Case based learning versus traditional didactic lecture in Community Medicine to teach vector borne diseases “malaria and dengue”: interventional study - Kadam, Deepali Mohan; Sejao, Aarti Vidyasindhu (International Journal Of Community Medicine And Public Health, 2019)
Background: Traditional didactic lectures do not evoke interactive teaching. Analytical thinking is not fostered. When students are put into the role of primary care physician, a sense of responsibility towards society is instilled in them generating a desire to learn. Case based learning (CBL) is one such method which can be used for meaningful learning. Incorporation of case based scenarios on real life situations in teaching can make medical undergraduate students competent to diagnose and treat common health problems. Methods: The study was conducted amongst third M.B.B.S. students. Interventional study design was used. Intervention group was taught with CBL and control group with didactic method. Pre-test, post-test was conducted to assess cognitive domain scores. To assess perception regarding CBL, feedback questionnaire was given to students. Percentages, unpaired t test were used for statistical analysis. Results: 99.60% of students perceived CBL is helpful to understand key concepts. 95.65% reported its importance in development of critical thinking. 95.66% reported that CBL session promoted meaningful learning as compared to lecture. On application of statistical tests, there was no difference in average marks scored by students taught with CBL as compared to those taught with traditional didactic method. Conclusions: This study demonstrates that CBL arouses interest. It can be incorporated to teach topics in Community Medicine.